Sphenoid wing meningioma mimicking the clinical presentation of stroke / Mohd Yusaini Mohd Yusri ... [et al.] - Mohd Yusri, Mohd Yusaini; Badlishah-Sham, Siti Fatimah; Peter, Alan Basil; Liew, Boon Seng (Faculty of Medicine, 2023)
Meningioma is the commonest extra-axial brain tumour in adults presenting with symptoms depending on the sites of its occurrence. We report an uncommon presentation of a meningioma in which a 57-year-old woman presented with a 3-day history of sudden onset of left-sided hemiparesis mimicking a stroke. Radiological imaging revealed an extra-axial lesion in the right sphenoid wing suggestive of a meningioma with perilesional oedema, mass effect, midline shift and herniation. She underwent surgical resection with histopathological examination revealing a meningioma World Health Organization (WHO) Grade I. Six weeks post operatively during follow-up, the left sided weakness had resolved, and patient has had no further symptoms of stroke until now.